2022
DOI: 10.23859/estr-211029
|View full text |Cite
|
Sign up to set email alerts
|

Study isssues of invasive species of the genus Solidago

Abstract: The impact of invasive species on the ecosystems belongs to the most important environmental problems. Representatives of the genus Solidago actively invade various plant communities. About 2300 literary sources were analyzed in order to determine the main tasks for the researchers of invasive species of this genus and to highlight the most relevant issues. Ambiguous evidence of the inhibitory effect of goldenrod on native flora species has been observed. Some studies report on the invasion of species of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…For example, the invasive plant Brassica juncea is highly effective at accumulating Pb in its tissues and has been used in several successful phytoremediation projects [124,125]. Other invasive plants, such as Robinia pseudoacacia and Solidago canadensis, have also been found to have high Pb tolerance and may have the potential for use in phytoremediation [126,127]. These plants are able to remove large amounts of Pb from contaminated soils, making phytoremediation an effective strategy for remediating Pb-contaminated sites.…”
Section: Potential Applicationsmentioning
confidence: 99%
“…For example, the invasive plant Brassica juncea is highly effective at accumulating Pb in its tissues and has been used in several successful phytoremediation projects [124,125]. Other invasive plants, such as Robinia pseudoacacia and Solidago canadensis, have also been found to have high Pb tolerance and may have the potential for use in phytoremediation [126,127]. These plants are able to remove large amounts of Pb from contaminated soils, making phytoremediation an effective strategy for remediating Pb-contaminated sites.…”
Section: Potential Applicationsmentioning
confidence: 99%
“…Once established, the population remained dominant over 30 years [ 8 , 17 , 18 , 19 , 20 ]. It was also reported that the species showed great impact on the native plant diversity in the introduced ranges [ 21 , 22 , 23 ]. Owing to the potential of the species for the rapid expansion and the formation of thick monospecific stands in the introduced ranges, as well as its impact on the environments, S. canadensis s.l.…”
Section: Introductionmentioning
confidence: 99%